(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
The protection of Traditional Knowledge (TK) and Traditional Cultural Expressions (TCEs) has gained significant attention in international legal and policy circles due to their socio-cultural and economic importance. Despite global efforts, there remains no universally accepted framework for the protection of TK and TCEs, leading to fragmented legal approaches across countries. This research examines the protection of TK and TCEs within existing intellectual property (IP) frameworks, focusing on the role of copyright law. Analyzing different models, the research finds that clear definitions of terms such as TK, TCEs, and Expressions of Folklore (EoF) would enhance judicial clarity and improve legal enforcement, especially within frameworks like the Indian Copyright Act.